2017
DOI: 10.1001/jamaoncol.2016.2638
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and the Risk of Fingerprint Loss

Abstract: Anticancer treatments are frequently accompanied by cutaneous adverse effects: capecitabine treatment induces handfoot syndrome (HFS) in approximately 50% to 60% of patients, whereas hand-foot skin reaction (HFSR) has been reported in 19% to 34% of patients treated with the tyrosine kinase inhibitors (TKIs) sunitinib malate or sorafenib tosylate. 1 Ultimately, these cutaneous adverse events are believed to result in the loss of fingerprints, which, to our knowledge, has been described anecdotally for patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 6 publications
3
36
0
2
Order By: Relevance
“…However, like other investigators, we observed that the fingerprint changes do not correlate with the occurrence or the grades of HFS . In one prospective cohort study, severe quality loss of fingerprints was reported in nine cases (14%) of 66 patients who were treated with capecitabine, but the HFS grade was not associated with the incidence of severe fingerprint quality loss .…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…However, like other investigators, we observed that the fingerprint changes do not correlate with the occurrence or the grades of HFS . In one prospective cohort study, severe quality loss of fingerprints was reported in nine cases (14%) of 66 patients who were treated with capecitabine, but the HFS grade was not associated with the incidence of severe fingerprint quality loss .…”
Section: Discussionsupporting
confidence: 59%
“…Changes or loss of finger lines is reported with the administration of other cancer drugs, such as paclitaxel (an anti‐microtubule chemotherapy agent) and sunitinib (a multi‐kinase inhibitor) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations